TEACHING ENGLISH WITH CUTTING-AGE TECHNOLOGIES IN 21TH CENTURY - Sherqulova Nodira; Inomjonova Farangiz; Formonova Marjona; Safarova Dildora (Ustozlar uchun, 2025)
This article explores the integration of cutting-edge technologies in English language teaching (ELT), highlighting how tools like artificial intelligence (AI), virtual reality (VR), and mobile applications enhance the learning experience and aid to boost studensʼ horizons. It examines the advantages of these technologies in making English language instruction more interactive, personalized, and accessible, ultimately improving language acquisition for diverse learners. Additionally, utilizing modern digital technologies in teaching can make a opportunity to improve students’ knowledge of technologies and how to use them in effective way